Measles and young adults: the case of the Local Health Authority of Bologna over the last decade. (30th September 2020) - Montalti, M; Gori, D; Dallolio, L; Catalani, F; Resi, D; Fantini, M P
Abstract: Background: Measles is increasing globally, with a 300% increase in the first three months of 2019 in the WHO European Region. Measles cases recorded annually over the last decade in Italy have been cyclical with the last peak in 2017 with 84 cases per million inhabitants. In the same year, national coercive vaccination measures were introduced for access to educational services. Although the country is again achieving adequate vaccination coverage (VC) for the second dose of MRR (93.2% in 2018), outbreaks can still occur in communities with low VCs. Methods: The aim of this study was to analyze measles epidemiology in Bologna Local Health Authority (LHA) from 2010 to 2018, focusing on age groups at higher risk of spread. Aggregate data on measles incidence were provided by Bologna HLA and VCs in residents were provided by the Emilia-Romagna Region (RER). Results: The number of cases in the period of reference was 261 cases, 240 of which were laboratory confirmed (92%). The overall average age was 28.5 years (standard deviation, ds: ±14.73 years). The age group with the highest average incidence rate was 20-24 years (93 per 1.000.000 inhabitants), followed by 25-29 years (88) and 30-34 years (75). With regard to occupation at highest risk of prevalence, students represented the largest group with 22.6% of cases. VC data in residents in RER showed that in the age group 19-35 the fraction of the population not vaccinated with two doses of vaccine decreased significantly in the birth cohorts of the 1990s with a coverage of 6.9% for the 1984 birth cohort. None of the cohorts taken into consideration achieved a VC of 95% for the second dose. Conclusions: Our results confirm the high proportion of measles cases among young adults. This highlights the need to consider catch-up actions and awareness campaign. For example, by focusing on students without previous documented vaccinations, considering that Bologna is home to tens of thousands of University students every year. Key messages: The measles epidemiology analysis in the Local Health Authority of Bologna (Italy) over the last decade showed that the young adults (aged 20-35) have the highest average incidence rate of measles. Considering the need to focus on young adults in order to contain new cases of measles; checks on previous vaccinations, catch-up actions and improved awareness campaign are essential.